Editors' Note: Long-term Neurologic Safety in Patients With B-Cell Lymphoma Treated With Anti-CD19 Chimeric Antigen Receptor T-Cell Therapy. (4th April 2023) - Lewis, Ariane; Galetta, Steven
Abstract : In "Long-term Neurologic Safety in Patients With B-Cell Lymphoma Treated With Anti-CD19 Chimeric Antigen Receptor (CAR) T-Cell Therapy, " Ursu et al. report that although 11 of 19 patients with refractory lymphoma developed acute neurotoxicity after treatment with CAR T-cell therapy and 0 of 19 had a change in cognitive performance or MRI 2 years after treatment. Karschnia et al. note that these findings must be interpreted cautiously given the small sample size and lack of additional treatment after CAR T-cell therapy, particularly given that other data demonstrate long-term visuospatial, cognitive, and neuropsychiatric symptoms after treatment with CAR T-cell therapy. In contrast, Tan et al. praise the study methodology and cite two other studies with similar findings. This discussion demonstrates the importance for future studies using CAR T-cell therapy to include long-term neuropsychological testing and a larger sample size.